Knowledge, attitude and practices in relation to prevention and control of schistosomiasis infection in Mwea Kirinyaga county, Kenya - J Mwai; S Njenga; M Barasa (BMC, 2016)
Abstract Background Schistosomiasis remains a major public health problem in Kenya. Inadequate knowledge, attitudes and practices (KAP) on causative factors are some of the critical factors for the increased prevalence. The study assessed KAP on the control and prevention of schistosomiasis infection in Mwea division, Kirinyaga County-Kenya. Four hundred and sixty five house-hold heads were enrolled in this study by use of simple random sampling technique. Methods The study employed an analytical descriptive cross sectional design utilizing both quantitative and qualitative data collection methods. A pretested structured questionnaire, Focus Group Discusions (FGDs) and Key Informant Interviews (KII) guides were used for data collection. Descriptive statistics and Chi square tests and Fisher's exact tests were computed where applicable. Data from the FGDs and KIIs were analyzed using NUID.IST NUIRO.6 software. Results Significant associations between knowledge and demographic factors i.e. age (p = 0.011), education level (p = 0.046), were reported. Handwashing after visiting the toilet (p = 0.001), having a toilet facility at home (p = 0.014); raring animals at home (p = 0.031), households being affected by floods (p = 0.005) and frequency of visits to the paddies (p = 0.037) had a significant association with respondents practices and schistosomiasis infection. Further significance was reported on households being affected by floods during the rainy season (p < 0.001), sources of water in a household (p < 0.047) and having a temporary water body in the area (p = 0.024) with increase in schistosomiasis infection. Results revealed that respondents practices were not significantly associated with gender (p = 0.060), marital status (p = 0.71), wearing of protective gear (p = 0.142) and working on the paddies (p = 0.144). Conclusions This study reveals that knowledge about the cause, transmission, symptoms and prevention of schistosomiasis among the Mwea population was inadequate, and that this could be a challenging obstacle to the elimination of schistosomiasis in these communities. Due to various dominant risk factors, different control strategies should be designed. Therefore, there is a need for integrated control programme to have a lasting impact on transmission of schistosomiasis infection. Control programs like mass drug administration need to go beyond anti-helminthic treatment and that there is a need of a more comprehensive approach including access to clean water, sanitation and hygiene. School and community-based health education is also imperative among these communities to significantly reduce the transmission and morbidity from schistosomiasis.